Resseguro: direito aplicável e formas de solução de conflitos - Teodoro, Viviane Rosolia (2023)
Reinsurance is a transfer from insurer of portion or total risk of the insurance policy or a set of these contracts to other parties. In simple words, it is an insurance for insurance entities. In claim events, reinsurance has the power to assures the solvency of an insurance company and reduces its capital requirements. The global reinsurance market is composed by major companies. It is based on customs of the reinsurance market. Reinsurance transactions share major risks on a global scale and the contracts between insurers and reinsurers must be governed by the good faith. Complementary Law n. 126 was sanctioned and approved in the beginning of 2007, opening the market for other national and foreign companies to start their reinsurance operations in the country and finished with the monopoly of the “Instituto de Resseguros do Brasil”. After 15 years of the opening of the reinsurance market, there are several doubts how it works, specially related to poor regulation of the government agencies and legal aspects of reinsurance contracts. The study about the reinsurance contract has the purpose to contribute to a better understanding of this institute in the national doctrine, through the analysis and discussion of its main legal aspects. The paper explores the main theories of insurance, coinsurance and reinsurance, its creation, historical evolution, the panorama of reinsurance activity in Brazil, its independence from insurance, legal nature, functions, typology, forms of contracting and main clauses, as well as the inclusion of reinsurance in the Insurance Law Project. Before introduce reinsurance in the context of international contracts and its main legal rules related, the thesis discusses about International Private Law. The applicable law to reinsurance contracts is explored, as well as the existence (or not) of ‘ freedom of choice for the parties of applicable law relate to the contracts, from the perspective of foreign and national law. A triple classification in terms of the rules is applicable to reinsurance contracts: what is explicitly stated in the contract, international customs, and the applicable national law. The essay explores the many principles, reinsurance customs and international standards or national legal systems. The international principles of reinsurance – PRICL, which serve as a source of interpretation, will be also investigated. At last, the thesis discusses the use of arbitration as a usual way to solve reinsurance disputes. Disputes between reinsurers and insurers are settle in arbitration, based on international standards, due to its contract complexity and not limited to a single country. Also, mediation is a plus and may be used in the interpretation of arbitration clauses inserted in the core of reinsurance contracts